The preliminary research of intercanine distance between humans and dogs by bite mark analysis - Yeong, Lee Deng; Dardjan, Murnisari; Susilawati, Sri; Oscandar, Fahmi; Rajion, Zainul Ahmad (Padjadjaran Journal of Dentistry, 2021)
Introduction: Bite marks between humans and dogs have a similar appearance and it becomes a challenge study for the dentist and forensic odontologists to discern between them. Intercanine distance (ICD) is one of the parameters to identify the biter species in humans and animals. The aim of this study was to analyse the differences of the ICD between humans and dogs. Methods: The analytical study design was done by measuring the ICD of bite marks in 65 humans and 22 dogs selected by purposive non-random sampling method with the inclusion criteria for human samples, students of Faculty of Dentistry Universitas Padjadjaran between 18 to 28 years old, canine occlusal relationship class I, presence of both intact canine teeth in each jaw, normal overjet and no diastema at the anterior teeth; and for dog samples, mesaticephalic skull shaped, having four intact canine teeth, and located across animal centres in Bandung. The gender and dental arch shape in humans and dogs were excluded. Human bite registrations were taken using wax pieces, while dog anterior teeth impressions were taken which were then casted with dental stone. The ICD was then measured using a digital vernier caliper with 0.01 mm resolution. The inter- and intra-observer variability calibrations were done before the sample measurements. The Mann-Whitney U statistical analysis was done to determine the significance between ICD of humans and dogs (p<0.05). Ethical clearance (No.1225/UN6.KEP/EC/2018) was obtained for both groups prior research study. Results: The statistical analytic showed, (p=0.0002) between humans and small and large sized dogs; (p=0.5093) for medium sized dogs in the maxillary. In the mandibula, showed (p=0.0002) between humans and small and large sized dogs; (p=0.0003) for medium sized dogs. Conclusion: The ICD analysed in this study were concluded to be different between humans and dogs (all sizes) in mandibular, humans and dogs (small and large sized) in maxillary. Conversely, the ICD between humans and medium sized dogs in maxillary were similar.